Prescribed burning in southwestern Australian forests. (1st August 2013) - Burrows, Neil; McCaw, Lachlan
Abstract : Prescribed burning is an important but often controversial fire‐management tool in fire‐prone regions of the world. Here, we explore the complex challenges of prescribing fire for multiple objectives in the eucalypt forests of southwestern Australia, which could be regarded as a model for temperate landscapes elsewhere. Prescribed fire has been used in a coordinated manner to manage fuels in Australia's eucalypt forests since the 1950s and continues to be an important tool for mitigating the impacts of unplanned wildfires on human society and on a broad range of ecosystem services. Prescribed fire is increasingly being used to manage fire regimes at the local and landscape scales to achieve biodiversity outcomes through maintenance of spatial and temporal patterns of post‐fire seral stages. The prescribed burning program in southwestern eucalypt forests has been informed by a long‐term program of applied research into fire behavior and fire ecology. To remain successful in the future, the prescribed burning program in this region will need to adapt to changing expectations of government and the community, emerging land‐use issues, resource limitations, and a drying climate.